Praktik Asketisme Pra Islam dan Rekonsiliasi terhadap Islamisasi di Gunung Kumbang, Brebes, Jawa Tengah (Abad XVI-XXI M) - Sunjana, Dani; Saringendyanti, Etty; Nugrahanto, Widyo (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Mount Kumbang, located in Ketanggungan Subdistrict, Brebes Regency, has been utilized as a site for ascetic practices since pre-Islamic times up to the present. This research aims to discuss the transition of ascetic practices due to Islamization on the slopes of Mount Kumbang from the 16th century to the present. The research focuses on the narrative of the encounter between pre-Islamic asceticism and Islamization, the forms of cultural reconciliation between pre-Islamic traditions and Islam, and how the ascetic community on Mount Kumbang has been politically portrayed in the process of Islamization. The historical method, encompassing heuristic processes, criticism, interpretation, and historiography, was employed in this research. The results demonstrate that the encounter between pre-Islamic asceticism and Islamization proceeded peacefully and was full of reconciliation. The narrative of Islamization and pre-Islamic asceticism appears in the "Babad Cirebon" and local folklore, which recount the continuation of ascetic traditions such as meditation practiced by Islamic disseminators on Mount Kumbang. Cultural reconciliation between pre-Islamic asceticism and Islamization is also evident in historical narratives, oral sources, and the culture of the community on the slopes of Mount Kumbang, such as taboos, the "ngasa" ritual, and religious practices that exhibit archaic characteristics and are well-documented in historical sources from both the colonial period and the present. The ascetic community has also politically contributed to Islamization by being portrayed as peacefully accepting Islamization, albeit not fully in its entirety. The ascetic community has been utilized as agents to depict the acceptance of Islam, even though it was not shown through perfect Islamic practices. The conclusion of this research indicates the continuity of ascetic practices from pre-Islamic traditions to Islamic traditions, as recorded in historical sources from the Islamic, colonial, and contemporary periods.